PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THREE STAY ONE STRAY (TSOS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SD NEGERI 005 RANTAU PANJANG KIRI KECAMATAN KUBU BABUSSALAM - Susanti, Dewi; Daud, Drs. H.Damanhuri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Problem Research is aimed at improving learning science students in the class III lessons in 2014/2015 by a Model cooperative learning type Three Stay One Stary (TSOS individually as well) overall student learning outcomes classical to class III to science SD 005 Rantau Panjang left side Babussalam sub-district. This research was done on 24 students. Data was collected through observation using sheets observation to cooperative learning data model type Three Stay One Stray (TSOS) through SCORES I and II for SCORES result data to learn. Student learning outcomes increased in the first cycle than it was before he had done action or before Currently PKT has served ship necessity in, But the increase student learning outcomes that happened before was held Currently PKT has served ship necessity in and after the cycle I that is 66.04 percent there is an increase of 11.23 percent while in the cycle both there is an increase of 7.57 percent by learning outcomes students of 71.04 percent. From the result of the research and discussion as outlined above learning model that by using cooperative type Three Stay One Stray (TSOS) is correct, then such teachers, students and student learning outcomes to increase and better. This information is proved that the hypothesis or which reads: with the implementation model cooperative learning type Three Stay One Stary (TSOS) can improve learning science students in grade primary school of 005 Rantau Panjang left side sub-district Babussalam"received."key words : cooperative learning type Three Stay One Stray, Learning